2017
DOI: 10.1002/2016jb013766
|View full text |Cite
|
Sign up to set email alerts
|

Self‐contained local broadband seismogeodetic early warning system: Detection and location

Abstract: Earthquake and local tsunami early warning is critical to mitigating adverse impacts of large‐magnitude earthquakes. An optimal system must rely on near‐source data to maximize warning time. To this end, we have developed a self‐contained seismogeodetic early warning system employing an optimal combination of high‐frequency information from strong‐motion accelerometers and low‐frequency information from collocated Global Navigation Satellite Systems (GNSS) instruments to estimate real‐time displacements and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Therefore, a seismic trigger is required to determine the onset of the coseismic phase. Ideally, this can be obtained by collocation (within ∼3–4 km) of strong motion accelerometers and GNSS instruments (Emore et al., 2007; Goldberg & Bock, 2017). A seismogeodetic combination of GNSS and accelerometer data (Bock et al., 2011) allows P wave detection from seismic velocities, while improving the precision of the displacement waveforms during seismic motion (Bock et al., 2004; Saunders et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a seismic trigger is required to determine the onset of the coseismic phase. Ideally, this can be obtained by collocation (within ∼3–4 km) of strong motion accelerometers and GNSS instruments (Emore et al., 2007; Goldberg & Bock, 2017). A seismogeodetic combination of GNSS and accelerometer data (Bock et al., 2011) allows P wave detection from seismic velocities, while improving the precision of the displacement waveforms during seismic motion (Bock et al., 2004; Saunders et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Where real-time GNSS receivers and accelerometers are collocated (defined as ≤ 1:5 km apart), these data can be synthesized to produce a seismogeodetic displacement time series that records the P-wave arrival, dynamic motions, and static offsets (Bock et al, 2011) with substantially lower noise than displacements calculated from GNSS data alone. Using data from accelerometers collocated with drilled-braced GNSS monuments, Goldberg and Bock (2017) resolved displacements sufficiently small to detect M w ∼ 5 events. Crowell et al (2013) found that a magnitude scaling relationship that used the peak displacement amplitude (Pd) measured during the first 5 s of seismogeodetic time series showed less magnitude saturation with similar latency compared with the one based on displacement from doubly integrated, high-pass-filtered accelerometer data alone.…”
Section: Gnss Network Upgrades In Support Of Shakealertmentioning
confidence: 99%
“…Earthquake detection is a fundamental step in a broad scope of seismological tasks (Aiken et al., 2018; Beaucé et al., 2019; Frohlich et al., 1982; Goldberg & Bock, 2017; Hauksson et al., 2017; Reverso et al., 2015; Simons et al., 2006; Skoumal et al., 2016; ten Brink et al., 2020; Yoon et al., 2017). Despite major improvements in seismic instrumentation, conventional detection approaches become increasingly challenging in view of (1) a significant increase in the volume of seismogram databases, (2) the low signal‐to‐noise ratios (S/Ns) associated with low‐magnitude earthquakes, which are often beyond the visual detectability, and (3) the occurrence of a massive number of earthquakes with small magnitudes.…”
Section: Introductionmentioning
confidence: 99%